Radiological outcomes following surgical fixation with wires versus moulded cast for patients with a dorsally displaced fracture of the distal radius: a radiographic analysis from the DRAFFT2 trial - Caroline E. Plant; Alexander Ooms; Jonathan A. Cook; Matthew L. Costa; on behalf of the DRAFFT2 collaborators (Bone & Joint Open, 2024)
Aims: The primary aim of this study was to report the radiological outcomes of patients with a dorsally displaced distal radius fracture who were randomized to a moulded cast or surgical fixation with wires following manipulation and closed reduction of their fracture. The secondary aim was to correlate radiological outcomes with patient-reported outcome measures (PROMs) in the year following injury. Methods: Participants were recruited as part of DRAFFT2, a UK multicentre clinical trial. Participants were aged 16 years or over with a dorsally displaced distal radius fracture, and were eligible for the trial if they needed a manipulation of their fracture, as recommended by their treating surgeon. Participants were randomly allocated on a 1:1 ratio to moulded cast or Kirschner wires after manipulation of the fracture in the operating theatre. Standard posteroanterior and lateral radiographs were performed in the radiology department of participating centres at the time of the patient’s initial assessment in the emergency department and six weeks postoperatively. Intraoperative fluoroscopic images taken at the time of fracture reduction were also assessed. Results: Patients treated with surgical fixation with wires had less dorsal angulation of the radius versus those treated in a moulded cast at six weeks after manipulation of the fracture; the mean difference of -4.13° was statistically significant (95% confidence interval 5.82 to -2.45). There was no evidence of a difference in radial shortening. However, there was no correlation between these radiological measurements and PROMs at any timepoint in the 12 months post-injury. Conclusion: For patients with a dorsally displaced distal radius fracture treated with a closed manipulation, surgical fixation with wires leads to less dorsal angulation on radiographs at six weeks compared with patients treated in a moulded plaster cast alone. However, the difference in dorsal angulation was small and did not correlate with patient-reported pain and function. Cite this article: Bone Jt Open 2024;5(2):132–138.